A Search and Shrink Approach for the Baseline Constrained LAMBDA Method: Experimental Results - Giorgi, G.; Teunissen, Peter; Buist, P. (Curran Associates, 2008)
In this paper we present experimental results of a new approach for resolving GNSS baseline constrained integer ambiguities. The method is based on a modification ofthe LAMBDA method, where the a-priori information on the baseline length is exploited in the search process. The integer ambiguity vector is searched by means of a processing strategy which iteratively reduces the size of the search space, resulting in fast convergence to the sought for solution. The Search and Shrink strategy is explained and numerical diagnostics are presented to illustrate its performance. Our results are based on simulated as well as on actual GNSS data and focus on single-frequency, single epoch processing, which is considered the most challenging case of GNSS attitude determination.